From City Branding Narratives to Consumer Experience: The Role of Culinary SMEs in Shaping City Image - Fahrian Arsyam Gultom; Eureka Try Zarazwanty R. Laega; Nurhasni Muis (Business Research and Administration Innovation, 2026)
Culinary-based city branding has increasingly been adopted as a strategic approach to enhance urban competitiveness and local economic development. This study aims to examine the role of culinary small and medium-sized enterprises (SMEs) in translating the city branding narrative of “Makassar Kota Makan Enak” into tangible consumer experiences. Employing a qualitative descriptive approach, this study is based on document analysis of official government publications, tourism reports, and relevant academic literature. The findings indicate that culinary SMEs function as strategic actors in shaping the experiential dimension of city branding by directly interacting with consumers and visitors. The effectiveness of the city branding initiative is influenced not only by the consistency of branding messages at the policy level, but also by the degree of alignment between branding narratives and everyday business practices of SMEs. Structural challenges, including limited branding literacy and uneven business capacity, may contribute to potential misalignment between brand promises and consumer experiences. This study contributes conceptually to the city branding and SME branding literature by emphasizing the importance of alignment between macro-level branding narratives and micro-level business practices. The findings highlight the need for collaborative and facilitative approaches in strengthening culinary-based city branding initiatives.